MANAJEMEN DAN KEPEMIMPINAN MADRASAH - Akib D., Muh. (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2012)
Abstract: Management activities covering a broad spectrum, starting from determining organization direction, creating organization activities, encouraging cooperation establishment, as well as supervizing the activities. Management has strategic roles, especially to help the organization meet the goals in utilizing equipment, land, office, product, service, and human relations. Educational leadership at the school level is based on the democratization concept, tasks specialization, authority delegation, professionalism, and tasks integration. Leadership that takes place in educational institutions means running leadership processes that are affecting personnel resources of education. Management and implementation of leadership in Islamic schools (madrassa) are expected to synchronize the various inputs or synergize all components in the learning process among teachers, students and support facilities both inside and outside the classrooms. Abstrak: Aktivitas manajemen mencakup spektrum luas, dimulai dari menentukan arah organisasi, menciptakan kegiatan organisasi, mendorong terbinanya kerjasama, serta mengawasi kegiatan. Manajemen memiliki peranan strategis, terutama untuk membantu pencapaian tujuan dalam mendayagunakan peralatan, lahan, kantor, produk, pelayanan, dan hubungan manusia dalam organisasi. Kepemimpinan pendidikan di madrasah dilandasi konsep demokratisasi, spesialisasi tugas, pendelegasian wewenang, profesionalitas, dan integrasi tugas. Kepemimpinan yang berlangsung pada lembaga pendidikan berarti menjalankan proses kepemimpinan yang sifatnya mempengaruhi sumber daya personel pendidikan. Manajemen madrasah dan pelaksanaan kepemimpinan di madrasah diharapkan mampu mensinkronkan berbagai input atau mensinergikan semua komponen dalam proses pembelajaran, baik antara guru, siswa dan sarana pendukung di kelas dan di luar kelas.